Optimization of processing parameters for the microencapsulation of soursop (Annona muricata L.) leaves extract: Morphology, physicochemical and antioxidant properties - Jordán-Suárez, Oscar (2021)
Soursop leaves contain bioactive compounds which degrade after being separated from their native matrix. In order to protect their functionality, encapsulation can be applied. This investigation aimed to optimize the parameters for microencapsulating a hydroethanolic extract of soursop leaves after selecting a technique among freeze (FDM) and spray drying (SDM). Selection was performed through a factorial design (23) including as factors: the technique (FDM and SDM), the encapsulant (Gum Arabic and maltodextrin) and its concentration (5% and 10%), for maximizing encapsulation efficiency (EE). Spray drying microencapsulation with maltodextrin at 10% showed the highest EE. Subsequently, the drying temperature and the feeding rate were optimized through a multilevel factorial design to minimize moisture and to maximize the powder solubility and the EE. A significant effect on the response variables (p < 0.05) was found, resulting in 140 ºC and 7 mL/min as optimum parameters. Optimized treatment powder was characterized in terms of microstructure (spherical particles with a random size and irregular surfaces), annonacin content via HPTLC (0.904 ± 0.054 mg/g), color (L* 66.89 ± 0.67, a* 0.06 ± 0.56 and b* 6.01 ± 0.20) and antioxidant capacity (17.88 ± 0.86 and 90.59 ± 1.19 µmol ET/g, by DPPH and ABTS assays). Proposed SDM conditions could be taken into account for preserving bioactive compounds from soursop leaves.